Effects of the uv-a irradiation on the freshwater prawn (Macrobrachium nipponense De Haan) and the greasy back shrimp (Metapenaeus ensis De Haan) reproductions - Binh, Doan Viet; Vinh, Nguyen Thi; Kim Dung, Nguyen Thi; Quyen, Nguyen Van (Academia Journal of Biology, 2014)
This article describes our research on effects of the UVA irradiation on prawn reproduction in order to find a method to stimulate the ovarian maturation and enhance the reproductive output of the prawn. In this study, the freshwater prawns Macrobrachium nipponense de Haan, were irradiated with UV-A light in 1 h, 2 h or 6 h/day continuously for 30 days. The greasy back shrimes Metapenaeus ensis de Haan, were irradiated also with UVA light in 2 or 3 h/day continuously for 20 days. The results indicated that the UVA irradiation had a pronounced effect on the prawn reproduction. The freshwater prawns exposed to UVA light in 2 h per day have increased the gravid percent, the clutch size, the hatching success and the estradiol and progesterone concentrations in their ovary. The irradiated greasy back shrimps with the same dose (2 h/day) have also increased the gravid percent and the hatching success in comparison with the not irradiated shrimps. These results should be further investigated to determine the ability of the UVA-irradiation application in the shrimp culture.